Low temperature decomposition of NO on ordered alumina films - Libuda, Jörg; et al. (Chemical Physics Letters, 2003)
We have investigated the interaction of NO with an ordered Al 2O3 film and a Pd/Al2O3 supported model catalyst, employing time-resolved IR reflection absorption spectroscopy (TR-IRAS) and molecular beam methods. It is observed that NO undergoes slow decomposition at low sample temperature, resulting in the formation of variety of NxOy surface species. The process involves strong structural transformations of the Al2O3 film. On Pd/Al2O3, decomposition of NO is found to be strongly suppressed. Based on the growth behavior of Pd nucleating at oxide defects, it is concluded that NO decomposition is preferentially initiated at specific defect sites on the alumina. © 2003 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2003.nat.dchph.ppc20.lowtem